Qualitative research a guide to design and implementation - Merriam, Sharan B. (The Jossey-Bass higher and adult education series, 2009)
This thoroughly revised and updated classic once again presents a practical guide to understanding, designing, and conducting a qualitative research study, as well as helps readers understand the theoretical and philosophical underpinnings of this research paradigm. The third edition includes new material on types of qualitative research; on the role of a theoretical framework in designing a study; a step-by-step guide to analyzing qualitative data; and an addendum for graduate students that provides a template for a thesis, dissertation, or grant application